2022
DOI: 10.37689/acta-ape/2022ar003397
|View full text |Cite
|
Sign up to set email alerts
|

Desinfecção de incubadoras usadas em Unidades de Cuidados Intensivos Neonatais: revisão integrativa

Abstract: Métodos: Revisão integrativa de literatura, realizada de junho a julho de 2020, nas bases de dados: LILACS, SciELO, CINAHL, SCOPUS, Web of Science e MEDLINE. Os achados foram organizados conforme o fluxograma PRISMA e discutidos de acordo com a literatura pertinente.Resultados: Dos 780 artigos encontrados, apenas cinco contemplaram os critérios de inclusão. Os saneantes utilizados foram: cloreto de didecildimetilamônio, polihexametilenobiguanida e Peróxido de Hidrogênio (VHP); cloreto de didecildimetilamônio; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…This would address the dual goals of supporting care partners' long‐term health and well‐being, as well as sustaining the caring role. These principles are echoed in recent work directly with older care partners 49 . A recently published integrative review of health promoting behaviours developed by informal caregivers of older adults reinforces the codesign panel findings regarding the broad range of resources needed for the maintenance of their overall health, well‐being, the improvement of quality of life and personal satisfaction 49 .…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…This would address the dual goals of supporting care partners' long‐term health and well‐being, as well as sustaining the caring role. These principles are echoed in recent work directly with older care partners 49 . A recently published integrative review of health promoting behaviours developed by informal caregivers of older adults reinforces the codesign panel findings regarding the broad range of resources needed for the maintenance of their overall health, well‐being, the improvement of quality of life and personal satisfaction 49 .…”
Section: Discussionmentioning
confidence: 87%
“…These principles are echoed in recent work directly with older care partners 49 . A recently published integrative review of health promoting behaviours developed by informal caregivers of older adults reinforces the codesign panel findings regarding the broad range of resources needed for the maintenance of their overall health, well‐being, the improvement of quality of life and personal satisfaction 49 . Among the needs carers identified that they wished to access, the search for information, family counselling, social, emotional and spiritual support stood out.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations